Software-assisted instruction, students' thinking level, and achievement in geometry - Guloya, Lorie Ann Benitez (2007)
This study sought the effects of the use of software and worksheets on students' achievement and Van Hiele levels of thinking skills in high school Geometry. Specifically, it determined whether or not students grouped according to their learning styles and exposed to software-assisted and conventional instruction differ in terms of thinking levels and achievement. Moreover, it identified and compared difficulties encountered by students exposed to such treatments. Lastly, it gathered data on the perceptions of students about the use of computers and software in learning Geometry. The sample, which consisted of 28 pairs of auditory, 10 pairs of visual, and eight (8) pairs of tactile/kinesthetic learners, was obtained from the third year high school students of a private school for girls in Quezon City. The instruments used to gather data were the Ottis-Lenon School Ability Test (OLSAT), a learning style inventory which was adopted from Kolb, researcher-made lesson plans on selected topics about Triangles, worksheets, Geometry Achievement Test (GAT) and Geometry Thinking Level Test (GTLT), and Opinionaire on Sketchpad. The two different groups into which the sample was divided were taught using conventional and software-assisted instruction. Parallel lesson plans were implemented except for the use of software in one group. Tests on achievement and thinking levels were given prior to and at the end of the four-week intervention. At the end of the intervention, the students' gain score in the GAT and Van Hiele levels of thinking skills were tested for significant difference using the Paired Samples t-Test and were found to be not statistically significant at 0.05 level of significance. Data on GAT and GTLT results of the three learning style groups - auditory, visual, and tactile/kinesthetic - were also analyzed and tested for significant difference using one-way analysis of variance and Wilcoxon Signed-Rank test. Data on students' difficulties and evaluation of the use of GSP were summarized and analyzed using qualitative methods.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Geometry -- Study and teaching (Secondary) -- Philippines -- Quezon City; Mathematical ability -- Testing; Geometry -- Study and teaching (Secondary) -- Computer-assisted instruction; Academic achievement -- Philippines -- Quezon City; Thought and thinking